Severe fever with thrombocytopenia syndrome complicated with aspergillus endocarditis and multiple organ infarctions after glucocorticoid treatment in an immunocompetent man: a case report - Yuxi Zhao; Xiaoxin Wu; Xinyu Wang; Lanjuan Li (BMC Infectious Diseases)
Abstract Background Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease characterized by leukopenia and thrombocytopenia, and aspergillosis is a common complication in severe cases. Previous studies have reported cases of SFTS complicated with invasive pulmonary aspergillosis (IPA) and central nervous system aspergillosis. Here, we present the first case of an immunocompetent patient with SFTS who progressed to IPA and Aspergillus endocarditis after glucocorticoid treatment, and embolism of the vegetations from the left ventricle led to multiple infarctions in the brain, kidney, and spleen. Case presentation A 66-year-old male farmer developed altered mental status during SFTS. His consciousness improved during the treatment of glucocorticoids, intravenous immunoglobulin, and ribavirin, but he developed embolisms in the spleen and right kidney, initially attributed to atrial fibrillation, and the anticoagulant agent was not administered due to the high risk of bleeding. Later, He was diagnosed with SFTS-associated IPA (SAPA), for which voriconazole was administered. However, he subsequently experienced a recurrence of altered mental status, accompanied by headache, blindness, and muscle weakness. Brain magnetic resonance imaging (MRI) revealed multiple cerebral embolisms and abscess. The echocardiography showed the vegetations in the left ventricle, suggesting multi-organ embolism caused by infective endocarditis (IE). Aspergillus fumigatus was confirmed through pathology and culture of the excised vegetations. The patient was eventually discharged with improved consciousness and muscle strength, but his vision showed minimal recovery. Conclusion Clinicians should be wary of aspergillosis in severe patients with SFTS, particularly those receiving glucocorticoid treatment. In patients with SAPA, cerebral aspergillosis and embolic stroke caused by Aspergillus endocarditis should also be considered when mental status alters. Furthermore, the possibility of Aspergillosis in other organs should be considered in high-risk patients.